A decision framework on the choice of management models for park and protected area tourism services. (June 2019) - Spenceley, Anna; Snyman, Susan; Eagles, Paul F.J.
Abstract: There are two categories of management approaches for the delivery of tourism services; insourcing or outsourcing. This paper presents a decision framework for the choice of a management model for the delivery of tourism-related services in protected areas. The research used the expert opinion of 28 PA senior tourism managers from the protected area and tourism authorities of 11 countries in the Southern Africa Development Community to identify the advantages and disadvantages of the use of 5 different management models for the delivery of tourism services: 1) outsourcing to private, profit-making companies; 2) outsourcing to a community; 3) outsourcing to a nongovernment organization; 4) outsourcing to a joint venture company; and, 5) insourcing to the PA authority. The comparisons utilized 7 themes: 1) finance; 2) tourism operations; 3) socioeconomic impact; 4) governance; 5) risk; 6) human resources; and, 7) environment and conservation. A total of 190 comparative findings were identified. The 28 senior tourism managers provided comments on the advantages and disadvantages of each management model according to all themes. These comments were summarized into a table of findings. The research found that all five management models are useful, but the decisions to choose the management model are highly influenced by the current legal and policy structure of the PA authority. This research provides information that can assist PA managers in the decision structure for the choice of and implementation of the various management approaches for the provision of tourism services in protected areas. This is the first paper of its kind to compare and analyse different management models using literature, research, as well as practitioners' experience and technical knowledge. Further research on all the models and the different potential options would be useful in providing a greater understanding of all the options to finance protected areas through tourism.